An effective short form of the 20-item University of California Los Angeles Loneliness Scale version 3: item response theory and network psychometrics - Jinyuan Liu; Hao Wu; Ming Chen; Ellen Lee; Xinlian Zhang; Shengjia Tu; Hanchang Cai (General Psychiatry)
Loneliness is a complex and usually unpleasant emotional response to isolation, which has been considered the latest global health epidemic exacerbated by the coronavirus disease 2019 pandemic, affecting nearly two-thirds of older adults. Some profound health implications carried by loneliness include depression, cognitive impairment, hypertension and frailty. Across the world, there is no consensus definition of loneliness, and its measure is based on the phenomenological perspective of the individual. The 20-item University of California Los Angeles Loneliness Scale version 3 (UCLA-20) is the most common measure. This scale demonstrates acceptable psychometric properties but is too long and complex for a phone interview. This paper addresses the increasing need to shorten this scale by adopting classical item response theory and network psychometrics to advance scale development. Through an item reduction analysis, we trimmed the original scale into an effective short form, which is as valid as the original one. With respondents’ time at a premium in most research nowadays, this short-form scale is an efficient and practical alternative to the original UCLA-20.